Energy for tomorrow's world : the realities, the real options, and the agenda for achievement - WEC Commission; World Energy Council (London : Kogan Page ; New York : St. Martin's Press, 1993)
This volume is the result of a unique project which set out to reconcile global views on the important energy issues confronting the world at present. All the important factors that affect the possibilities and limitations for future energy solutions are considered, be they economic, technical, environmental or social and institutional developments and constraints. The research has resulted in the World Energy Council identifying the key issues for continued energy development into the next century.
At head of title: World Energy Council.
Includes bibliogrphical references (p. [247]-262) and index.
oif 14/09/15
Loan
Keywords: Energy policy; Energy development; Energy consumption; Power resources -- Environmental aspects